Pengaruh Struktur Modal dan Kemampulabaan Terhadap Return Saham Perusahaan Properti dan Real Estate Yang Terdaftar di BEI Tahun 2013-2015 - Wadudi Wibowo; Ani Mekaniwati; Iriyadi Iriyadi (Jurnal Ilmiah Manajemen Kesatuan, 2020)
This research is to acknowledge the influence of capital structure and profitability to the stock returns of the listed real estate and property companies in BEI on 2013-2015. This research consists of two independent variables regarding capital structure and profitability, and one dependent variable regarding stock returns. Data used is secondary data which could be accessed from www.idx.co.id . The hypothesis testing in this research uses data panel regression model. The results are: 1) positive & significant results between DER towards capital returns 2) positive & significant results between NPM towards capital returns. The contributions for potential investors, this research was hoped to increase the knowledges of financial information of the companies specialised in real estate & properties sector. Also hoped to give good contributions to discussion on financial analysis particularly related with DER, NPM & capital returns. Keywords : capital structure, profitability, stock returns, and data panel regression